A new thermostable Cu(II) coordination polymer: photocatalytic activity and application values on diabetes. Issue 1 (1st January 2021) - Jin, Chen-Lu; Fang, Shao-Jun; Yu, Li; Guo, Zhen-Shan
ABSTRACT: A Cu(II) coordination polymer with the composition of [Cu2 (L)2 (4, 4ʹ-bipy)2 ]n ·2 n(ClO4 ) (1, HL = 4-methyl-L-phenylalanine and 4, 4ʹ-bipy is 4, 4ʹ-bipyridine), was successfully obtained by the reaction of the mixed ligand of HL and 4, 4ʹ-bipy with Cu(ClO4 )2 · 6H2 O under solvothermal condition. The as-synthesized compound not only has high thermal stability until 275°C but also excellent photocatalytic activity for the methyl blue solution degradation under the irradiation of ultraviolet light. Furthermore, the compound's treatment activity on the diabetes was determined and its relevant mechanism was also studied. The cytotoxicity or hemolysis toxicity (HC50) of the synthesized compound was also evaluated in this research.